Comparison Functions and Fixed Point Results in Partial Metric Spaces - Nawab Hussain; Zoran Kadelburg; Stojan Radenović; Falleh Al-Solamy (Abstract and Applied Analysis)
The aim of this article is to clearly formulate various possible assumptions for a comparison function in contractive conditions and to deduce respective (common) fixed point results in partial metric spaces. Since standard metric spaces are special cases, these results also apply for them. We will show by examples that there exist situations when a partial metric result can be applied, while the standard metric one cannot.